A first year and first semester project-led Engineering Education approach - Mesquita, Diana (2009)
This paper describes the organization model of a Project-Led Education (PLE) process carried out in the Industrial Management and Engineering (IME) programme at the University of Minho. It intends to analyse the PLE approach in the first year and first semester, according to the perceptions of the coordination team involved in the 2008/09 PLE edition. The emerging data from a group discussion with all coordination team members revealed a set of dimensions which allow a better understanding of the way the process is organized and how it could be improved. The constraints found were mainly three: first, teachers feel that in this process they have much more work than in traditional methodologies; second, some aspects of lack of suitable interdisciplinarity between subjects were identified; and finally some doubts in regard to learning outcomes were raised and some suggestions of individual activities were proposed. Therefore, a set of improvement changes will be presented in order to overcome some of the difficulties identified by faculty staff. These changes will be taken in account in the design of the next PLE edition (2009/10).